Goal Achievement Failure Drives Corticospinal Modulation in Promotion and Prevention Contexts - Lo Gerfo, Emanuele; Pisoni, Alberto; Ottone, Stefania; Ponzano, Ferruccio; Zarri, Luca; Vergallito, Alessandra; Varoli, Erica; Fedeli, Davide; Romero Lauro, Leonor J. (Frontiers in Behavioral Neuroscience, 2018)
When making decisions, people are typically differently sensitive to gains and losses according to the motivational context in which the choice is performed. As hypothesized by Regulatory Focus Theory (RFT), indeed, goals are supposed to change in relation to the set of possible outcomes. In particular, in a promotion context, the goal is achieving the maximal gain, whereas in a prevention context it turns into avoiding the greatest loss. We explored the neurophysiological counterpart of this phenomenon, by applying Transcranial Magnetic Stimulation (TMS) and recording the motor evoked potentials (MEPs) in participants taking part in an economic game, in which they observed actions conveying different goal attainment levels, framed in different motivational contexts. More than the real value of the economic exchange involved in the game, what affected motor cortex excitability was the goal attainment failure, corresponding to not achieving the maximal payoff in a promotion context and not avoiding the greatest snatch in a prevention context. Therefore, the results provide support for the key predictions of RFT, identifying a neural signature for the goal attainment failure.